Apropriações transitórias do espaço público : a paisagem e os ambulantes no Centro de Vitória, ES - Lima, Glaucio Coutinho de (2011)
The theme of this work refers to the appropriation of public space that occurs with transient temporality, within less than 24 hours. Your objective is to provide an understanding of these usages, characteristic of the central areas of Brazilian cities, a